2017
DOI: 10.1002/htj.21262
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Study of the Reduction of Energy Consumption through the Exchanger Coupled Conventional Air‐Ground‐Air Conditioner. Application to the Building

Abstract: In this study, a new method of using the earth‐air heat exchangers to reduce energy consumption in buildings is discussed. The idea is to couple the EAHE with the condenser of a residential air conditioning system to enhance the effectiveness of the latter. Under the climatic conditions of high temperature in summer (south‐eastern region of Algeria), which can sometimes exceed 50 °C, what makes the heat exchange between the air conditioner and the external environment very difficult in addition to the problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the opinion of Fazlikhani et al [15], the EAHE system saves a great deal of energy, improves the average air temperature outlet the EAHE, and also reduces temperature fluctuations. Benhamza et al [16] reported a significant decrease in the energy consumption by the EAHE system, an increase in the efficiency and performance factor of air conditioning, compared to direct utilization of an air conditioner. Maoz et al [17] disclosed that the EAHE system with tube length ranging 50 to 70 m, diameter between 18 to 25 cm, and air speed between 5 to 7 m/s, can lower the temperature by about 15 to 18°C, and can be used to cool a single room.…”
Section: Introductionmentioning
confidence: 99%
“…In the opinion of Fazlikhani et al [15], the EAHE system saves a great deal of energy, improves the average air temperature outlet the EAHE, and also reduces temperature fluctuations. Benhamza et al [16] reported a significant decrease in the energy consumption by the EAHE system, an increase in the efficiency and performance factor of air conditioning, compared to direct utilization of an air conditioner. Maoz et al [17] disclosed that the EAHE system with tube length ranging 50 to 70 m, diameter between 18 to 25 cm, and air speed between 5 to 7 m/s, can lower the temperature by about 15 to 18°C, and can be used to cool a single room.…”
Section: Introductionmentioning
confidence: 99%
“…A new convective ground resistance was added for a peclet number greater than 0.01. 46 Some studies are based on combined systems where EAHE is coupled with evaporative coolers, desiccant dehumidification systems (experimentally 47,48 as well as numerically , [49][50][51][52] and vapor compression systems 42,53,54 to improve its competence in the air conditioning industry. Energy savings of 71%, 49 74%, 55 and 75% 56 and CO 2 emissions savings of 76 to 91% 52 have been reported in coupled systems.…”
Section: Introductionmentioning
confidence: 99%